Konseptualisasi dan Peluang Cyber Notary dalam Hukum - Putri, Cyndiarnis Cahyaning; Budiono, Abdul Rachmad (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2019)
This paper aims to reveal the conceptualization and opportunity of the concept of the cyber notary as one of the other notary authorities as stated in the explanation of Article 15 Section (3) of Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning Position of Notary Public (UUJN). This paper is a normative study using the statute approach and conceptual approach. The concept of a cyber notary can be interpreted as a method for a notary in carrying out their duties and authorities by using electronic equipment (cyber), but their authority has limitations for the authority of certification of transactions conducted electronically. Opportunities for the concept of a cyber notary can be reviewed in the drafting of the results of the General Meeting of Shareholders based on Article 77 of Law Number 40 of 2007 concerning Limited Liability Companies and storage of the Notary protocol in electronic form. The application of cyber notary is still constrained by UUJN which has not yet opened up opportunities for deed making through electronic media.